40Ar/39Ar ages and zircon petrochronology for the rear arc of the Izu-Bonin-Marianas intra-oceanic subduction zone - Schmitt, Axel Karl; Konrad, Kevin; Andrews, Graham D. M.; Horie, Kenji; Brown, Sarah R.; Koppers, Anthony A. P.; Pecha, Mark; Busby, Cathy J.; Tamura, Yoshihiko (International geology review, 2017)
Long-lived intra-oceanic arcs of Izu-Bonin-Marianas (IBM)-type are built on thick, granodioritic crust formed in the absence of pre-existing continental crust. International Ocean Discovery Program Expedition 350, Site U1437, explored the IBM rear arc to better understand continental crust formation in arcs. Detailed petrochronological (U-Pb geochronology combined with trace elements, oxygen and hafnium isotopes) characterizations of zircon from Site U1437 were carried out, taking care to exclude potential contaminants by (1) comparison of zircon ages with ship-board palaeomagnetic and biostratigraphic ages and 40Ar/39Ar geochronology, (2) analysing zircon from drill muds for comparison, (3) selectively carrying out in situ analysis in petrographic thin sections, and (4) minimizing potential laboratory contamination through using pristine equipment during mineral separation. The youngest zircon ages in Site U1437 are consistent with 40Ar/39Ar and shipboard ages to a depth of 1390 m below sea floor (mbsf) where Igneous Unit Ig 1 yielded an 40Ar/39Ar age of 12.9 ± 0.3 Ma (all errors 2σ). One single zircon (age 15.4 ± 1.0 Ma) was recovered from the deepest lithostratigraphic unit drilled, Unit VII (1459.80-1806.5 mbsf). Site U1437 zircon trace element compositions are distinct from those of oceanic and continental arc environments and differ from those generated in thick oceanic crust (Iceland-type) where low-δ18O evolved melts are produced via re-melting of hydrothermally altered mafic rocks. Ti-in-zircon model temperatures are lower than for mid-ocean ridge rocks, in agreement with low zircon saturation temperatures, suggestive of low-temperature, hydrous melt sources. Zircon oxygen (δ18O = 3.3-6.0‰) and hafnium (εHf = + 10-+16) isotopic compositions indicate asthenospheric mantle sources. Trace element and isotopic differences between zircon from Site U1437 rear-arc rocks and the Hadean detrital zircon population suggest that preserved Hadean zircon crystals were probably generated in an environment different from modern oceanic convergent margins underlain by depleted mantle.
Im Titel sind die Zahlen 40 und 39 hochgestellt
Published online: 06 Sep 2017
Gesehen am 01.04.2020